Interhemispheric somatosensory differences in chronic pain reflect abnormality of the Healthy side - Harrington, Flavia; Stanton, T.R.; Moseley, G.L.; Lotze, M.; Mcauley, J.H. (WILEY, 2015)
© 2014 Wiley Periodicals, Inc. It is widely accepted that complex regional pain syndrome (CRPS) is associated with shrinkage of the primary somatosensory cortex (S1) representation of the affected limb. However, supporting evidence is surprisingly limited and may be compromised by high risk of bias. This study compared the S1 spatial representation of the hand in 17 patients with upper-limb CRPS to 16 healthy controls, using functional MRI. Innocuous vibration was delivered to digits one (D1) and five (D5) in a block-design. Resultant activation maxima were located within a bilateral S1 mask, determined a priori. Distance between D1 and D5 activation maxima, calculated for both hands, was used as a measure of S1 representation. Analyses were blinded to group and hand. In patients, S1 representation was smaller for the affected hand than it was for the healthy hand (t(11)=2.02, P=0.03), as predicted. However, S1 representation of the affected hand was no different to that of either hand in controls. Critically, S1 representation of the healthy hand of patients was larger than that of controls' hands. CRPS seems to be associated with an enlarged representation of the healthy hand, not a smaller representation of the affected hand. These findings raise important questions about neuroplasticity in CRPS.